On Discrete Solutions for Elliptic Pseudo-Differential Equations - Tarasova, O.A.; Vasilyev, A.V.; Vasilyev, V.B. (Bulletin of the Karaganda University. Mathematics Series, 2021)
We consider discrete analogue for simplest boundary value problem for elliptic pseudo-differential equation in a half-space with Dirichlet boundary condition in Sobolev-Slobodetskii spaces. Based on the theory of discrete boundary value problems for elliptic pseudo-differential equations we give a comparison between discrete and continuous solutions for certain model boundary value problem.